Fuzzy logic for thermal process - Mohd Naim bin Mohd Zaini, Mohd Naim (2009)
The main purpose of this project is to compare the performance of current proportional-integral-derivative (PID) method that widely used in industry with the Fuzzy Logic Control as an alternative.